Time dependent deterioration of mitochondrial oxidative capacity in heart transplantat recipients with type 2 diabetes mellitus. (14th October 2021) - Moos, C; Scheiber, D; Zweck, E; Horn, P; Boeken, U; Akhyari, P; Kelm, M; Roden, M; Szendroedi, J; Westenfeld, R
Abstract: Background: Diabetic cardiomyopathy is defined as Heart failure in patients with Type 2 Diabetes (T2DM) in absence of traditional risk factors. Following HTX, a substantial number of recipients develop insulin resistance or T2DM, associated with cardiac allograft vasculopathy and with increased mortality. Recently we have shown that endomyocardial biopsies of heart transplant (HTX) recipients with T2DM express reduced mitochondrial respiration. Purpose: The current study analyses time depended impact of T2DM on myocardial mitochondrial respiration of a priorly non-diabetic heart. We hypothesized that myocardial mitochondrial oxidative phosphorylation capacity declines in patients with T2DM compared to glucose tolerant heart transplant recipients and that reduced mitochondrial respiration leads to impairment of cardiac function. Methods: We included 101 HTX recipients who underwent routine endomyocardial biopsy. Patients with T1DM or a Donor with DM were excluded. Patients were classified according to criteria of the American Diabetes Association as non-diabetic (n=23), prediabetic (n=38) or T2DM (n=40), by either Fasting Plasma Glucose, 2h Plasma Glucose, HbA1c or intake of antidiabetic medication. We performed ex vivo high resolution respirometry on permeabilized fibres to assess myocardial mitochondrial respiration. Left ventricular ejection fraction (LV-EF) was assessed by cardiac-MRI or Echocardiography. Results: Groups were of comparable age (p=0.06), sex (p=0.25) and time since HTX (p=0.91). Mean time since HTX was 29 months. Current rejection episodes (p=0.37) or corticoid pulse therapy (p=0.46) did not significantly differ between groups. Linear regression in T2DM patients revealed an inverse relationship between time since HTX and mitochondrial respiration at state III conditions supported by the substrates octanoyl-carnitine and ADP (R 2 =0.16, F(1, 38)=6.97, p=0.01). Regression analyses for non-DM group and Prediabetes group revealed no significant relationship between time since HTX and mitochondrial function (non-DM: R 2 =0.04, F(1, 21)=0.9, p=0.35; Prediabetes: R 2 =0.01, F(1, 36)=0.27, p=0.61). Exclusion of patients with cellular allograft rejection (ISHLT ≥1) or of patients with recent corticoid pulse therapy did not alter these results. Linear correlation revealed a significant relationship (r=0.33, p=0.04) between declining mitochondrial state III respiration and left ventricular ejection fraction (n=39), suggesting associated functional consequences. Conclusions: Our results suggest a T2DM associated decline of mitochondrial oxidative capacity in HTX recipients. Reduced mitochondrial respiration is associated to lower LV-EF. Targeting mitochondrial respiration might be a promising novel therapeutic approach to address T2DM associated mortality. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Research Counsil